Analisis Kinerja Jalan Perintis Kemerdekaan Kota Pontianak Setelah Pembangunan Jembatan Paralel Landak II - Ranty Christiana; Syarifah Melly Maulina (Fakultas Teknik, 2023)
Perintis Kemerdekaan road is a connecting road for people who will use the Bridge of Kapuas and Landak. The government has realized the addition of a new bridge construction as a duplicate which is located right next to the Landak Bridge. The Landak II Bridge was completed in April 2019 and has been operating in August 2019. People still cannot feel comfortable in using traffic. The construction of the Landak II parallel bridge has not solved the problem of increasing the volume of vehicles in Pontianak. Because of these transportation problems, the researchers tried to analyze the performance of the Perintis Kemerdekaan road. The purposes of this researches are (1) to determine the changes in the performance of the road section used for traffic flow on the Perintis Kemerdekaan road in 2022 after the operation of the Landak II Bridge. (2) Provide an overview of the recommendations for handling impacts that are carried out to overcome road performance problems. The research method used is descriptive and quantitative methods. The results showed that the level of service for the Perintis Kemerdekaan road after the Landak II bridge was built was at level E where the current was unstable and the speed sometimes stopped.